PENERAPAN FILSAFAT ILMU TERHADAP ILMU HUKUM - Irwansyah; Rika Afrida Yanti (LPPM-IAI BATAM, 2023)
The existence of law science is still often questioned its validity as a disciplinary study, both among social scientists and legal scientists. There are those who argue that law science does exist with its own characteristics, while other opinions question that if legal knowledge exists, what science is it based on. Because the science of law has very unique characteristics, it is different from other sciences. Law science has normative, practical and prescriptive characteristics and characteristics. With its normative nature, it passes by, so that it is neglected from the nature of science which has empirical characteristics. For this reason, the existence of legal science must be examined in depth so that the existence of legal science can be accepted as a science or vice versa. So there is an appropriate study to see the essence and existence of law science, it can be seen from a philosophical perspective, how to view the view of law science, and how the application of legal science. As it is known that science is the parent of the other sciences. The theoretical basis that will be discussed regarding aspects of ontology, epistemology and philosophical axiology.